2013
DOI: 10.2174/1875414701305010001
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Properties and Chemical Composition of Conyza Aegyptiaca (L.) Oil: Studies on Two Dipterous Insect Pests

Abstract: Abstract:The herb, Conyza aegyptiaca L., was subjected to hydrodistillation process to extract the essential oil from the whole dry plant material. Larvae and adult stages of the mosquito, Anopheles pharoensis, and the housefly, Musca domestica, were used as test model organisms representing two dipterous insect pests of medical importance. Under standard bioassay test methods, the LC50 of the oil accounted to 37.8 ppm and 0.087 mg/cm 2 against larvae and adults of An. pharoensis, respectively. These toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Larvicidal bioassay was done in accordance to Mansour and Mohamed (2013) using 20 larvae in the presence of 100 g of semisynthetic diet (described above) with 50 ml water containing the tested concentrations of the extracts (0.5, 1, 2, 3 g/ L). Mortality was recorded at 24, 48, and 72 h after treatment during which any change in mobility and appearance of larvae was noted down.…”
Section: Larval Feeding Bioassaymentioning
confidence: 99%
“…Larvicidal bioassay was done in accordance to Mansour and Mohamed (2013) using 20 larvae in the presence of 100 g of semisynthetic diet (described above) with 50 ml water containing the tested concentrations of the extracts (0.5, 1, 2, 3 g/ L). Mortality was recorded at 24, 48, and 72 h after treatment during which any change in mobility and appearance of larvae was noted down.…”
Section: Larval Feeding Bioassaymentioning
confidence: 99%
“…In Togo, a large part of the population continues to use plants remedies for their primary healthcare (Kpodar et al, 2016), including the management of central nervous system disorders (Kantati et al, 2016). Conyza aegyptiaca is one of these medicinal plants of Togolese flora, whose scientific studies have revealed its antioxidant potential through its antimicrobial (Anani et al, 2000), antihypertensive and cardioprotective (Kpegba et al, 2011), antimalarials and insecticides (Mansour and Mohamed, 2013), and antihyperglycemic's properties (Akakpo et al, 2016(Akakpo et al, , 2017. However, none of these scientific studies have focused on its neuroactive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed satisfactory results from the use of several essential oils for the house fly M. domestica management (Abdel Halim and Morsy, 2005;Sinthusiri and Soonwera, 2013;Pinto et al, 2015). In addition, the synergistic action of essential oils with conventional chemical pesticide previously studied (Mansour and Mohamed, 2013).…”
Section: Introductionmentioning
confidence: 99%